2018
DOI: 10.1038/s41426-018-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Subinhibitory concentrations of resveratrol reduce alpha-hemolysin production in Staphylococcus aureus isolates by downregulating saeRS

Abstract: Resveratrol is a natural phytoalexin. In recent studies, it has been shown to have beneficial effects on cardiovascular disease and cancer and has been deemed to have effective antiviral and immunomodulatory activities. Methicillin-resistant Staphylococcus aureus is a multidrug-resistant pathogen associated with skin and soft tissue infections. Alpha-hemolysin is known to play a key role in the symptoms caused by S. aureus, and the saeRS two-component system has been shown to be a major regulatory system of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…By RT-PCR, we found that the subinhibitory concentrations of fusidic acid down-regulated the expression of saeRS at the mRNA level. This is consistent with previous research in our laboratory (Duan et al, 2018;Jin et al, 2018) in that saeRS can downregulate the production of α-toxin. For the part of the biofilm, it was found by the crystal violet staining method that the S. aureus biofilm with fusidic acid was down-regulated, which is consistent with the previous study (Siala et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…By RT-PCR, we found that the subinhibitory concentrations of fusidic acid down-regulated the expression of saeRS at the mRNA level. This is consistent with previous research in our laboratory (Duan et al, 2018;Jin et al, 2018) in that saeRS can downregulate the production of α-toxin. For the part of the biofilm, it was found by the crystal violet staining method that the S. aureus biofilm with fusidic acid was down-regulated, which is consistent with the previous study (Siala et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, it has been reported in the literature that fusidic acid has an inhibitory effect on the biofilm formation of S. aureus (Siala et al, 2018), but the mechanism is not clear. Inspired by the subinhibitory concentrations of mupirocin and resveratrol, which can downregulate the virulence of S. aureus in our previous study (Duan et al, 2018;Jin et al, 2018), we attempted to study the effect of subinhibitory concentrations of fusidic acid on the virulence of S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accord with literature data. Duan et al [34] showed subinhibitory concentration of resveratrol decreased the expression of hla and inhibited the regulation of saeRS. Subinhibitory concentrations of thymol significantly inhibited the transcription of hla, sea, and seb in S. aureus and acted partly through the agr locus [35].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, bacteria are frequently exposed to Sub-MIC of the antimicrobial agent and these conditions could result in mutagenesis and release of microbial virulence factors (Andersson and Hughes, 2014;Jo and Ahn, 2016;Larsen et al, 2016;Huijbers et al, 2019). Thus, it is important to evaluate the effects of the antimicrobial agents in pathways related to mutagenesis and virulence (Hobdey et al, 2017;Duan et al, 2018). We first showed that EbEO did not induce the expression of recA which is the first gene in the SOS response.…”
Section: Discussionmentioning
confidence: 99%